Morphological and Anatomical Structural Features of Shoots of Species of the Genus Thymus L., Introduced in Botanical Garden of Lviv National University Named After Ivan Franko - Hrytsyna, Myroslava; Skybitska, Mariya; Salamon, Ivan (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The aim of work is the exploration of morphological and anatomical features of species of genus Thymus L., which are exhibited at a ‘medical plants’ collection in Вotanical Garden of Ivan Franko National University of Lviv, namely Th. vulgaris L., Th. zygis L., Th. camphoratus Hoffmanns. Link, Th. callieri Borb. Anatomical structure studies of a lamina of leaves were conducted with the help of ‘Leica DM 500’ microscope. Raw of species of genus Thymus is aboveground mass on a stage of flowering. In explored species leaves are contrary crisscrossed, in the lower part of sprout they are small petioled and upwards they become sedentary. The pattern of the lamina is changed in a similar way. In all species, these laminas are wrapped up. Pubescence of leaves is made of simple, non-glandular hairs and glandular essential oils (capitate and peltate) trichomes. Leaves Th. vulgaris are lanceolate, dark green above, wrapped below, where they are gray from dense pubescence with simple, unicellular, curved hairs. Leaves of Th. zygis are grey because of thick pubescence. It is created of a single cell, upwards sharpened hairs, and two-cell <a href="https://context.reverso.net/%D0%BF%D0%B5%D1%80%D0%B5%D0%B2%D0%BE%D0%B4/%D0%B0%D0%BD%D0%B3%D0%BB%D0%B8%D0%B9%D1%81%D0%BA%D0%B8%D0%B9-%D1%80%D1%83%D1%81%D1%81%D0%BA%D0%B8%D0%B9/may+be+geniculately+curved">curved hairs, where three cellular hairs can be met. In Th. callieri leaves are green, over the edge of lamina they have pubescence of long, 5–7 cellular impacted hairs and between them short, 1–3 cellular hairs are situated. Simple hairs also are situated along veins as well. In all of the species capitate trichomes are situated on the surface of a lamina. Except this, on the surface of lamina essential peltate hairs with multicellular glands are situated. Cells of the upper epidermis of Th. vulgaris and Th. zygis they are oval, Th. callieri has epidermis cells with winding walls. The stomata apparatus is of a diacetate type. The amount of stomata is bigger from the abaxial side than from adaxial surface leaves. Essential oil fittings are situated above big veins in mesophile of a leaf. Their numerous cells contain thick cytoplasmic content. The mesophyll is formed from spongy tissue, which has 1 large and, rarely, 2 small essential oil containers (Th. vulgaris). Other species have 3–5 essential oil fittings. All species formed inflorescence of the compleх tassel. The apex of inflorescences grows monopodially. It is racemous (open). The partial inflorescences are dichasium and located in the axils of opposite leaves. The calyx is сampanullate with unevenly lobed and pubescent teeth of the lower lip. The corolla is double-lobed, formed from 5 grown petals.